Cartography of productions in History of Education in Graduate Programs in Education in the state of Pará (2005-2018) - Alves, Laura Maria Silva Araújo (2019)
This paper aimed to build a cartography about academic productions made on history of education in the State of Pará, which is based on the theses and dissertations of the graduate programs in education of UFPA and UEPA in the period 2005-2018. The cartography allowed to evaluate the advances in the scientific production relative to the history of education in the Amazon, as well as to identify gaps and challenges to the researchers of education of that region. The productions of theses and dissertations show significant productions in the field of history of education, even though there is no specific line or nucleus in the two graduate programs. At the end, we analyzed to what extent the two programs have contributed to the strengthening of research in History of Education.